A systematic review of large animal models of combined traumatic brain injury and hemorrhagic shock - Mayer, Andrew R. (Neurosci Biobehav Rev, 2019)
Traumatic brain injury (TBI) and severe blood loss (SBL) frequently co-occur in human trauma, resulting in high levels of mortality and morbidity. Importantly, each of the individual post-injury cascades is characterized by complex and potentially opposing pathophysiological responses, complicating optimal resuscitation and therapeutic approaches. Large animal models of poly-neurotrauma closely mimic human physiology, but a systematic literature review of published models has been lacking. The current review suggests a relative paucity of large animal poly-neurotrauma studies (N = 52), with meta-statistics revealing trends for animal species (exclusively swine), characteristics (use of single biological sex, use of juveniles) and TBI models. Although most studies have targeted blood loss volumes of 35–45%, the associated mortality rates are much lower relative to Class III/IV human trauma. This discrepancy may result from potentially mitigating experimental factors (e.g., mechanical ventilation prior to or during injury, pausing/resuming blood loss based on physiological parameters, administration of small volume fluid resuscitation) that are rarely associated with human trauma, highlighting the need for additional work in this area.